Perinatal behavioral patterns during and after human-animal interactions in rangeland breeding ewes - Schiller, Kaleiah; Horback, Kristina (Frontiers in Animal Science, 2024)
Consistent individual behavioral differences (CIDs) among livestock are known to be inherent qualities of the animal that are repeatable over time and across contexts and can be related to production. Shepherds rely on qualities of the ewe to promote lamb health, survival, and performance, and selecting ewes based on desirable phenotypes may be one way to benefit lamb outcome. Previous research indicates that traits observed among breeding ewes in restrained contexts during human-animal interactions (HAIs) may have a greater association with maternal care and lamb outcome than responses in an open testing environment. The current study investigated the relationship between several behaviors in multiparous ewes (n = 42) in two distinct contexts: 1) human-animal interactions, with no lamb present, during post-breeding, gestation, and weaning, which were performed three times per year for 2 years (six trials in total), and 2) HAIs, with the lamb present, after parturition once per year for 2 years (two trials in total). Tests without the lamb present included a Human Contact, Presence, and Approach test within each of the six trials, and tests with the lamb present included a Lamb Handling and Tie Down test. General additive models with a random term for individual were used to investigate the relationship between behaviors from outside of the lambing season to behaviors within the lambing season. The proportion of time in the ‘peripheral zone’ in the Human Presence test, at post-breeding, was a significant negative predictor of ‘environmental vigilance’ (i.e., being on look-out rather than attending to lamb) in the Lamb Tie Down test (P=0.02). A post-hoc negative relationship was found between ‘environmental vigilance’ and ‘sniffing/grooming’ the lamb in the Lamb Tie Down test. In addition, sheep who were more environmentally vigilant in the Lamb Tie Down test were less avoidant of the human in the Human Presence test (post-breeding). Weaning weights, yet not birth weights, were highly repeatable within ewes [R=0.70, P=0.001, CI(0.29, 0.91)], and weaning weight models were improved with the inclusion of time in the ‘peripheral zone’ in the Human Presence test and grooming and ‘environmental vigilance’ in the Lamb Tie Down test. Of note, the avoidance of the human, when the lamb was not present, was associated with weaning weights and therefore could be considered as a metric to consider when selecting ewes. Ewe behavior in response to humans outside of the lambing season be useful in gauging future maternal behavior (i.e., grooming) and lamb birth and weaning weights.